Atypical Temporal Dynamics of Resting State Shapes Stimulus-Evoked Activity in Depression—An EEG Study on Rest–Stimulus Interaction - Wolff, Annemnarie; de la Salle, Sara; Sorgini, Alana; Lynn, Emma; Blier, Pierre; Knott, Verner; Northoff, Georg (Frontiers in Psychiatry, 2019)
Major depressive disorder (MDD) is a complex psychiatric disorder characterized by changes in both resting state and stimulus-induced activity. Whether resting state changes are carried over to stimulus-induced activity, however, is unclear. We conducted a combined rest (3 mins) and task (mismatch negativity paradigm) EEG study in n=28 acute depressed MDD patients, comparing them with n=25 healthy participants. Our focus was on the temporal dynamics of both resting state and stimulus-induced activity for which reason we measured peak frequency (PF), coefficient of variation (CV), Lempel-Ziv complexity (LZC), and trial-to-trial variability (TTV). Our main findings are: (i) atypical temporal dynamics in resting state, specifically in the alpha and theta bands as measured by peak frequency (PF), coefficient of variation (CV) and power; (ii) decreased reactivity to external deviant stimuli as measured by decreased changes in stimulus-induced variance and complexity – TTV, LZC, and power and frequency sliding (FS, PS); (iii) correlation of stimulus related measures (TTV, LZC, PS, FS) with resting state measures. Together, our findings show that resting state dynamics alone are atypical in MDD and, even more important, strongly shapes the dynamics of subsequent stimulus-induced activity. We thus conclude that MDD can be characterized by an atypical temporal dynamic of its rest-stimulus interaction; that, in turn, makes it difficult for depressed patients to react to relevant stimuli such as the deviant tone in our paradigm.